(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The palaearctic Deltocephalinae Anoplotettix fuscovenosus (Ferrari) was investigated in the vineyard agro-ecosystem in Piedmont. Morphological features of adult, egg and nymphs are reported. Juvenile instars and adults live on different plants: larvae and nymphs on wild herbaceaus monocotyledons and dicotyledons, adults on fruit, grapevine, and climbing and bushy plants and on broadleaf trees in waste areas. Among cultivated plants, Vitis vinifera Linnaeus risulted t be the most appreciated one. This phloem plant sucker showed to accomplish one generation per year and to overwinter as eggs under the bark of grapevine canes. Owing to its capacity to transmit phytoplasmas and its great polyphagy, A. fuscovenosus requires further researches to clarify its true role as a vector of phytopathogenic agents in both vineyards and fruit-grove agro-ecosystems.